2016
DOI: 10.1002/jbm.b.33723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short glass fibers on the polymerization shrinkage stress of dental composite

Abstract: This study examines contraction stresses of seven short fiber reinforced composites (sFRC) exhibiting different volume loads and aspect ratios (AR)* of fibres. The shift towards a greater utilization of posterior resin composites in dentistry has seen increased interest in the use of randomly oriented short glass fibers in these restorative materials. While the effect of these fibers on modulus, strength, and toughness has been studied, very little information exists on their effect on polymerization shrinkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…This is interesting and could be attributed to the potential light transmitting capacity of the short glass fibers inside the canal as well as the greater transparency observed in SFRC material. This finding is in line with the result of curing depth performed in the study by Shouha and Ellakwa, which showed that SFRC exhibited the deepest cure (6.7 mm) in comparison with different conventional PFC composites 49) . Previous studies have also shown that FRCs conduct and scatter the light better than conventional PFC composites 47,50) .…”
Section: Discussionsupporting
confidence: 90%
“…This is interesting and could be attributed to the potential light transmitting capacity of the short glass fibers inside the canal as well as the greater transparency observed in SFRC material. This finding is in line with the result of curing depth performed in the study by Shouha and Ellakwa, which showed that SFRC exhibited the deepest cure (6.7 mm) in comparison with different conventional PFC composites 49) . Previous studies have also shown that FRCs conduct and scatter the light better than conventional PFC composites 47,50) .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Shouha and Ellakwa reported that SFRC exhibited the deepest cure (6.7 mm) in comparison with different composite resins . This was explained by the effect of relatively well‐aligned millimeter‐scale fibers down the narrow mold enhancing light penetration, as well as the greater transiency observed in SFRC materials .…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, Shouha and Ellakwa reported that the addition of 5 wt% of short fiber fillers to resin matrix did not effect polymerization shrinkage stress values, whereas 10 and 20 wt% loading resulted in higher stress values . According to Shouha and Ellakwa, an increase in shrinkage stress from the fiber load of >5 wt% could arise predominantly from increases in modulus and stiffness of the material.…”
Section: Resultsmentioning
confidence: 99%
“…46 Other studies showed that EverX Posterior developed either similar or higher polymerization stress and gap formation in vitro compared to other bulk-fill materials. 3,50 Strategy 2B: Self-healing composites…”
Section: Strategy 2a: Fiber-reinforced Compositesmentioning
confidence: 99%